Chalcomycins from Marine-Derived Streptomyces sp. and Their Antimicrobial Activities - Jiang, Shutai (Mar Drugs, 2017)
Dihydrochalcomycin (1) and chalcomycin (2), two known chalcomycins, and chalcomycin E (3), a new compound, were isolated from marine-derived Streptomyces sp. HK-2006-1. Their structures were elucidated by detailed spectroscopic and X-ray crystallographic analysis. The antimicrobial activities against Staphylococcus aureus, Escherichia coli, Candida albicans, and Aspergillus niger of 1–3 were evaluated. Compounds 1–2 exhibited activities against S. aureus with minimal inhibitory concentrations (MICs) of 32 µg/mL and 4 µg/mL, respectively. The fact that 1–2 showed stronger activity against S. aureus 209P than 3 indicated that the epoxy unit was important for antimicrobial activity. This structure–activity tendency of chalcomycins against S. aureus is different from that of aldgamycins reported in our previous research, which provide a valuable example for the phenomenon that 16-membered macrolides with different sugars do not have parallel structure–activity relationships.